SURVEI KEPUASAAN MASYARAKAT TERHADAP PENGGUNAAN BIOGAS SAMPAH DI GAMPONG JAWA KECAMATAN KUTARAJA KOTA BANDA ACEH - Novia Zalmita; Riza Miranda; M Hafizul Furqan (Geography Education Study Program, Universitas Samudra, 2022)
Biogas is an energy resource in the form of natural gas produced through piles of organic waste. Biogas is given free of charge to people with an average middle to lower economic level to meet their needs. This study focuses on a survey of community satisfaction with the use of biogas waste. The purpose of this study was to determine community satisfaction with the use of biogas waste in Gampong Jawa, Kutaraja District, Banda Aceh City. The population in this study were 210 biogas recipient households and from the total population, 21 samples were assigned to each biogas receiving household. Data collection techniques in this study using questionnaires and observation techniques. Data processing techniques using descriptive techniques and simple statistical formulas. Based on the results of the questionnaire, the percentage of answers very dissatisfied was 4.11%, dissatisfied at 12.81%, quite satisfied at 45.65%, satisfied at 32.51%, and very satisfied at 4.92%. So it can be concluded that in general the community is satisfied with the use of biogas waste in Gampong Jawa, Kutaraja District, Banda Aceh City